Assessment of Design Strategies and Economic Viability for Sanitary Landfill Planning Using GIS and AHP: A Case Study of Shuklagandaki Municipality, Nepal - Dhakal, Sushil; Khanal, Santosh; Adhikari, Sundar; Aryal, Rajendra (Journal of Advanced College of Engineering and Management, 2026)
The planning of sanitary landfills in emerging municipalities repeatedly hurts from a disjointed approach, where site suitability analysis is dissociate from comprehensive context-specific design strategies and economic viability assessment, leading to plans that are technically infeasible or economically unviable owing to limited integration between spatial appropriateness, engineering design, and lifecycle cost assessment . This research targets to bridge this gap by evolving an integrated framework for sanitary landfill planning, employed to Shuklagandaki Municipality, Nepal. The methodology integrates Geographic Information Systems (GIS) and the Analytical Hierarchy Process (AHP) for multi-criteria site selection, along with waste generation projections, engineering design calculations, and a lifecycle cost analysis. The most noteworthy results show that only 0.89% (1.489 km²) of the municipal area is highly appropriate for landfill planning with land use, residential proximity, and water body protection being the most weighted criteria. The design for a 15-year facility approves a mineral liner system and estimates a peak leachate generation of 0.125 m³/day, while the economic assessment reveals a serious dependency on establishing a dedicated waste management fee to bear substantial annual operation and closure costs. The major conclusion is that while suitable sites and feasible designs exist, sustainable implementation is reliant upon integrating spatial planning with pragmatic engineering and securing institutional commitment to long-standing financial mechanisms, providing a replicable model for evidence-based landfill planning in analogous constrained environments.